A novel method for alumina preparation by electrotransformation AlCl3 solution under NH4Cl-catalyzed and CO2-injected conditions - Han X.-X.; Liu Y.-M.; Yang L.-X.; Lu Y.-F.; Wang R.-T.; Zhang T.-A. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2022)
As a refractory industrial solid waste, high-alumina fly ash is discharged into nature in large quantities, causing serious environmental harm. The extraction of valuable components, such as aluminum, from high-alumina fly ash has become a research hotspot at home and abroad. The shortcomings of traditional alumina extraction from high-alumina fly ash include long technological processes, large amounts of waste acid and alkali, and serious equipment corrosion. A novel method for alumina preparation by electrotransformation AlCl3 solution(EAS) under NH4Cl catalysis with injected CO2 has been proposed by Northeastern University. The process has advantages, such as short flow and no waste acid discharge. In this study, the influence of initial NH4Cl concentration in the cathodic chamber on solution pH, phase and morphology of electrotransformation products, phase, D(50) and D(90) of roasting products, and Al recovery rate were examined. Simultaneously, EAS was examined and compared with and without injected CO2, as well as EAS under NH4Cl catalysis with and without injected CO2. The results showed that, when the solution in the cathodic chamber was NH4Cl with CO2 injection, with electrotransformation time extension, pH increased slowly and the morphology of electrotransformation products were all rough and fluffy block structures. Increasing initial NH4Cl concentration effectively improved the product crystallization states, roasting products D(50) and D(90), and Al recovery rate.